Making sense of phrasal verbs - Shovel, Martin (English Languaje Teaching, 1992)
Acquiring an understanding of phrasal verbs so essentail for a fluent command of spoken english. Can be a tedious bussiness. Not sp with this book. Making sense of phrasal verbs presents some of the most common verbs through lively cartoon ilustrations and guides learners to an understanding of their meanings with carefully worded cue questions